TREATMENT AND MANAGEMENT FOR SUICIDE ATTEMPT - Yagatheeswaran Ketheeswaran (Faculty of Medicine, Udayana University, 2013)
Suicidal behavior is a leading cause of injury and death worldwide. Suicide attempt is more prevalent among men, whereas nonfatal suicidal behaviours are more prevalent among women and persons who are young, are unmarried, or have a psychiatric disorder. Despite an increase in the treatment of suicidal persons over the past decade, incidence rates of suicidal behavior have remained largely unchanged.